Associations between obesity and cognitive impairment in the Chinese elderly: an observational study - Hou Q (Dove Medical Press, 2019)
Qingtao Hou,1,* Yang Guan,1,* Weihua Yu,2 Xintong Liu,1 Lihua Wu,2 Mingzhao Xiao,3 Yang Lü1 1Department of Geriatrics, The First Affiliated Hospital of Chongqing Medical University, Chongqing, People’s Republic of China; 2Department of Anatomy, Institute of Neuroscience, Chongqing Medical University, Chongqing, People’s Republic of China; 3Department of Urology, The First Affiliated Hospital of Chongqing Medical University, Chongqing, People’s Republic of China *These authors contributed equally to this work Purpose: The aim of this study was to investigate the relationship between obesity and cognitive impairment in the Chinese elderly.Patients and methods: Patients aged 60 years or above were enrolled from the Department of Geriatrics of The First Affiliated Hospital of Chongqing Medical University from March 2013 to May 2017. Mini-Mental State Examination scale was used to assess the cognitive function. Body mass index (BMI) and waist–hip ratio were used to classify obesity. Student’s t-test, Mann–Whitney U-test, or chi-squared test was used to compare the data between participants with normal cognition and participants with cognitive impairment as appropriate. Univariate logistic regression models and multivariate logistic regression models were performed to explore the relationship between BMI or abdominal obesity and cognitive impairment.Results: A total of 1,100 patients including 568 men and 532 women aged 60–98 years (median age 79 years) were enrolled. After adjusting for age, gender, smoking, drinking, education level, hypercholesterolemia, hypertension, and diabetes, overweight was significantly associated with a decreased risk of cognitive impairment (OR=0.458, 95% CI=0.298–0.703, P<0.001). After adjustment for age, education level, hypercholesterolemia, hypertension, and diabetes, abdominal obesity remained significantly associated with an increased risk of cognitive impairment (OR=1.532, 95% CI=1.037–2.263, P=0.032).Conclusion: Overweight is associated with a decreased risk of cognitive impairment in the Chinese elderly, while abdominal obesity is associated with an increased risk of cognitive impairment independent of conventional sociodemographic, lifestyle, and health-related comorbid factors. Keywords: body mass index, cognitive function, elderly, waist-hip ratio